Edukasi Kesehatan Mata Untuk Pencegahan Miopia Pada Remaja di SMA Kartika XIX-2 - Theophylia Melisa Manumara; Muhammad Deri Ramadhan; Wizyanti Salma Azizah; Selpiyanti Selpiyanti; Dinna Alifia; Hernina Hernina; Tika Aliyah; Zenina Noer Fadilah; Windi Ispiyani; Pitriyani Pitriyani; Carla Youlanda (Jurnal Medika: Medika, 2026)
Myopia is a refractive disorder in which the parallel rays that come to the eye in an unaccommodating state are refracted at a single point in front of the retina. Risk factors for myopia are genetics, behavioral factors for reading books, watching TV, and using gadgets. Myopia is often experienced by students at the secondary school level compared to other age groups. The purpose of this activity is to increase knowledge and awareness about Myopia through health education at Kartika XIX-2 High School by involving 30 students in this health education activity. The method used is an educational method by providing Health Education on Eye Health among adolescents. The results of the implementation of this activity in the form of increasing knowledge about eye health are evidenced by the results of the post test on students who can answer well. This shows the effectiveness of health education with educational methods that can increase students' knowledge of Myopia. Increasing knowledge, it is hoped that students can play a more active role in maintaining eye health. This activity emphasizes the importance of education about myopia among adolescents, to reduce the progressivity of Myopia and increase awareness of Myopia prevention.